Simulasi Penanganan Potensi Aliran Debris Di Gunung Sago (Studi Kasus Di Batang Lakin, Kecamatan Lareh Sago Halaban, Kabupaten Lima Puluh Kota) - Sutikno, Sigit; Hadthya, Reinhart '; Sujatmoko, Bambang ' (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The regions in foothills of Sago mountain are flood-prone area due to debris flow. As occurred on March 22, 2010, there has been a catastrophic overflow of debris flow from Sago mountain. The disaster resulted in severe damage around the rivers downstream Sago mountains, including Batang Lakin river. This research study debris flow potential and how to mitigate it in Batang Lakin river, West Sumatra. Analysis of potential debris flow hazard of Batang Lakin river and alternative debris mitigation is simulated using the debris flow simulator Kanako 2D version 2.051. Simulation is important for verifying effect of controlling flow of debris prior to construction work carried out. Rain data input was calculated based on fifty years time period and one hundred years time period Research findings show that at Batang Lakin river, debris flow occurred and overflowing river channel. Alternative countermeasure chosen is sabo dam. For fifty years period when debris flow peak discharge of 59.50 m3/second required 2 units of sabo dams (closed type) with positions at Sta 0 +200 (Sabo height 6 m) and at Sta 0 +450 (Sabo height 4 m). For one hundred years period when debris flow peak discharge of 62.66 m3/second required 2 units of sabo dams (closed type) with positions at Sta 0 +200 (Sabo height 6 m) and at Sta 0 +450 (Sabo height 5 m) to prevent overflow of debris flow to the settlement. Thus, the right efforts to control debris flow on Batang Lakin is the sabo dam. Keyword : debris flow, effective prevention, Sago mountain, sabo dam.